Getting started in private practice : the complete guide to building your mental health practice - Stout, Chris E. (Getting Started., 2005)
This comprehensive, "How To" book offers the tips and tools necessary to build a successful private mental health practice from the ground up. This "hands-on" guide provides sample business and marketing plans, as well as checklists, sidebars, and simple mathematical formulas for determining service rates, revenues, return on investment, and more.